BUSINESS ETHICS AND SIMPLE BOOKKEEPING TRAINING FOR SMEs OWNERS IN THE SIWALANKERTO VILLAGE, SURABAYA CITY (Universitas Wijayakusuma Purwokerto, 2023)
Business Ethics and Simple Bookkeeping Training for SMEs Owners in the Siwalankerto Village, Surabaya City, is a form of optimizing and improving the soft skills of SMEs. In business ethics, training will be carried out on how to carry out business processes so that they comply with business ethics rules and do not cause ethical problems for SMEs in the future. Meanwhile, simple bookkeeping is carried out to provide MSME discipline in recording financial income and expenses. The purpose of Community Service by providing Simple Business Ethics and Bookkeeping Training for Small and Medium Enterprises (SMEs) in the Siwalankerto Village, Surabaya City, is to assist these SMEs in increasing awareness of the rules of business ethics and increasing discipline in the financial records of SMEs. The specific targets in the Business Ethics and Simple Bookkeeping Training activities for SMEs are to produce: 1) Increasing awareness of the rules of business ethics and 2) Increasing discipline in financial records. It is hoped that with the Simple Business Ethics and Bookkeeping Training for SMEs, a society will be formed that is capable of carrying out business processes by correct ethical principles and improving financial records in an orderly manner.